Attitudes towards linguistic purism in Croatia: Evaluating efforts at language reform - Peti-Stantić, Anita; Langston, Keith (2003)
The authors discuss the contemporary language policy in Croatia and give results of a questionnaire that was conducted in 10% of Croatian schools in order to evaluate language competence of teachers.
Projekt MZOS
ENG